Entre o sacerdócio e a pesquisa histórica: a trajetória de padre Luiz Sponchiado na Quarta Colônia de imigração italiana - RS - Manfio, Juliana Maria (2015)
The present work was part of the activities performed in the History Post Graduation Program at the Federal University of Santa Maria, with the assistance of CAPES/DS. The theme of the research is the trajectory of Priest Luiz Sponchiado the Quarta Colônia, colonized region by a majority of Italians in the last nineteenth century. Through the concentration area "History, power and culture", the work approaches the relations of power and culture between a priest, society and culture of the Quarta Colonia. The dissertation is inserted into the line of research "Culture, Migration and Work", which propose a discussion on the transformation of a region of immigration & Italian colonization caused by an agent of the Catholic Church. The central objective is to understand how the priest acted and articulated their actions in the political and cultural camps in favor of building an "Italian identity on the Quarta Colônia". For this research, were the main fonts manuscripts Priest Luiz Sponchiado, the records of genealogy books produced by him, his correspondence, newspaper clippings, and other documents that are found in Central Genealogy Research (CPG Nova Palma).The sources analysis indicates how the priest built the history of the Quarta Colônia and as assisted in creating an identification between the residents of this region. In addition, there was a bibliographic dialogue with Italian immigration studies in RS and biography & trajectory. These discussions allow understand the trajectory of this priest became an important resource for the reconstitution of the historical context of events and the dynamics experienced by the Quarta Colônia, and the priest was able to act and transform the space in a very appropriate manner to the elaboration of an Italian identity matrix.